Genetic translation studies: An emerging discipline - Cordingley, Anthony; Montini, Chiara (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This article charts the emergence of a new form of translation research that we term genetic translation studies. It explores the foundations of this approach in the French school of critique génétique, which developed a methodology for studying the drafts, manuscripts and other working documents (avant-textes) of modern literary works with the aim of revealing the complexity of the creative processes engaged in their production. This methodology draws upon different theoretical and interdisciplinary approaches (poetic, linguistic, philosophical, psychoanalytical, phenomenological, etc.) and has since been adapted to the study of other media, including music, cinema, photography, painting, architecture, and the translated text. This article analyses how genetic approaches have been applied to translated texts by both genetic critics and translation scholars. It highlights, furthermore, the opportunities as well as the challenges for literary and other forms of translation research when a genetic approach is adopted.